[INVITED] Computational intelligence for smart laser materials processing. (1st March 2018) - Casalino, Giuseppe
Highlights: Description of the most used computational intelligences (CI) in manufacturing. Survey of the most recent applications of CI in laser materials processing (LMP). Identification of trends and opportunities in the use of CI in LMP. Abstract: Computational intelligence (CI) involves using a computer algorithm to capture hidden knowledge from data and to use them for training "intelligent machine" to make complex decisions without human intervention. As simulation is becoming more prevalent from design and planning to manufacturing and operations, laser material processing can also benefit from computer generating knowledge through soft computing. This work is a review of the state-of-the-art on the methodology and applications of CI in laser materials processing (LMP), which is nowadays receiving increasing interest from world class manufacturers and 4.0 industry. The focus is on the methods that have been proven effective and robust in solving several problems in welding, cutting, drilling, surface treating and additive manufacturing using the laser beam. After a basic description of the most common computational intelligences employed in manufacturing, four sections, namely, laser joining, machining, surface, and additive covered the most recent applications in the already extensive literature regarding the CI in LMP. Eventually, emerging trends and future challenges were identified and discussed.